Pengembangan Model Economic Production Quantity Mengakomodasi Continue dan Discrete Demand serta Kebijakan Rework Secara Simultan - Oktavia, Nurike; Henmaidi, Henmaidi; Fithri, Prima (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2020)
Inventory of finished goods needs to be planned and controlled regularly. Fulfilling customer demand whenever and wherever is the main purpose of the supply. This issue is related to production activities. Many companies use the Economic Production Quantity (EPQ) Model in determining the size of their lot productions. This model is able to show how to minimize total production costs by reducing inventory costs. Customer behavior at PT XYZ makes product delivery divided into 2 types. The first type, finished goods is sent continuously in small amounts called continue demand. The second type, products is sent between certain time intervals in large quantities called discrete demand. Basic EPQ Model’s parameters do not accommodate a system like this. In addition, PT XYZ requires rework for products that do not pass the quality test. Therefore, this research was developed to formulate EPQ model that can accommodate two types of demand, continue and discrete, as well as the existence of rework policy. This study tries to provide another approach in solving the derivation problem using the "Arithmetic-Geometric Mean" method. The results of this study will display a mathematical formulation to find the optimal production cycle time for PT XYZ. Numerical examples are discussed to show practical models.